Judicial systems in transition economies : - Anderson, James H. (The World Bank, 2005)
Judicial Systems in Transition Economies looks at the experience of countries in Central and Eastern Europe and the Baltics (CEE) and the Commonwealth of Independent States (CIS) as they reform their legal and judicial institutions to fit the needs of a market economy. The study shows, rather disturbingly, that less progress has been made in judicial reform than in most other areas of institutional reform in these countries.The transition from socialism to capitalism requires a fundamental reorientation of legal and judicial institutions. This study reviews the environment preceding reforms, forces that provoked and supported them, and the reform agendas undertaken in these countries since 1990. Against this background, it exposes the impact of reforms, implementation gaps, and the underlying determinants of success and failure.The report examines how courts have performed, and reveals their impact on public opinion and the business environment. It provides insight into linkages among reforms as well as linkages between reforms and public demand for a fair judiciary. The authors show that while each country presents different challenges and opportunities, certain lessons apply in most settings. Their insights and data would be useful to policy makers, judicial personnel, and those involved in reforming judiciaries.The study draws on numerous data sources. These include the World Bank, the European Bank for Reconstruction and Development (EBRD, the American Bar Association–Central European and Eurasian Law Initiative (ABA–CEELI), the World Values Survey, the World Economic Forum, and the University of Strathclyde.